Monotherapy of RAAS blockers and mobilization of aldosterone: A mechanistic perspective study in kidney disease. (1st February 2020) - Gupta, Gaurav; Dahiya, Rajiv; Singh, Yogendra; Mishra, Anurag; Verma, Aseem; Gothwal, Sunil Kumar; Aljabali, Alaa A.A.; Dureja, Harish; Prasher, Parteek; Negi, Poonam; Kapoor, Deepak N.; Goyal, Rohit; et al.
Abstract: In patients with acute kidney injury progressively converting into chronic kidney disease (CKD), proteinuria and high blood pressure predict progression to end-stage renal disease (ESRD). Although, Renin-angiotensin-aldosterone system (RAAS) regulates blood pressure and kidney disease through both direct and indirect mechanisms. RAAS blockers that act at the level of angiotensin or lower in the cascade can cause compensatory increases in the plasma renin and angiotensin II level. Here, in this review article, we are exploring the evidence-based on RAAS blockade action releases of aldosterone and hypothesizing the molecular mechanism for converting the acute kidney injury into chronic kidney disease to end-stage renal disease. Highlights: The RAAS is a critical regulator of blood volume and systemic vascular resistance. RAAS inhibitors prevent proteinuria, kidney fibrosis and the slow decline of renal function. RAAS inhibitors play a protective role in both the early and end stages of kidney disease.